2022
DOI: 10.31235/osf.io/uhvbp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Politics as Usual? Measuring Populism, Nationalism, and Authoritarianism in U.S. Presidential Campaigns (1952-2020) with Deep Neural Language Models

Abstract: Radical-right parties and candidates combine three discursive elements in their electoral appeals: anti-elite populism, exclusionary and declinist nationalism, and illiberal authoritarianism. Recent studies have explored whether these frames have diffused from radical-right to centrist parties in the latter's effort to compete for the former's voters. This paper investigates the obverse process: the radical right's (specifically, Donald Trump's) reliance on discursive elements that had long been present in mai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…I believe that this paper's lessons for theory building and measurement in the context of organizational ecology have broad implications for other work in sociology that seeks to build connections to cognition. This includes such diverse fields such as cultural sociology (DiMaggio, 1997;Mohr, Bail, Frye, Lena, Lizardo, McDonnell, Mische, Tavory, and Wherry, 2020;Vaisey, 2021;Cerulo, Leschziner, and Sheperd, 2021), economic sociology (Vila-Henninger, 2021), political sociology (Bonikowski, Luo, and Sthuler, 2022), and stratification (Kozlowski et al, 2019). Pursuing the new approach might not only improve theory and measurement in these fields, but it might also reveal deeper connections among them.…”
Section: Discussionmentioning
confidence: 99%
“…I believe that this paper's lessons for theory building and measurement in the context of organizational ecology have broad implications for other work in sociology that seeks to build connections to cognition. This includes such diverse fields such as cultural sociology (DiMaggio, 1997;Mohr, Bail, Frye, Lena, Lizardo, McDonnell, Mische, Tavory, and Wherry, 2020;Vaisey, 2021;Cerulo, Leschziner, and Sheperd, 2021), economic sociology (Vila-Henninger, 2021), political sociology (Bonikowski, Luo, and Sthuler, 2022), and stratification (Kozlowski et al, 2019). Pursuing the new approach might not only improve theory and measurement in these fields, but it might also reveal deeper connections among them.…”
Section: Discussionmentioning
confidence: 99%
“…To study the notions of “we” invoked by U.S. presidential candidates, I use a text corpus of campaign speeches and public statements created by Bonikowski and colleagues (2021). This data combines different sources to cover the elections from 1952 to 2020 and comprises 2,956 speeches delivered by 34 candidates.…”
Section: Applicationmentioning
confidence: 99%
“…Recent studies have shown populism and authoritarianism—two other central components of radical‐right appeals—to have a long history in mainstream U.S. politics (Bonikowski et al. 2022; Bonikowski and Gidron 2016; Dai and Kustov 2022; Fahey 2021). Given the ubiquity of nostalgia as a basic human sentiment, its efficacy as a political framing device, and the simple ways in which it can be evoked, its use in radical politics may have mainstream precedents as well.…”
Section: Mainstream Antecedents Of Radical‐right Discoursementioning
confidence: 99%
“…Sixth, our study examines the relationship between nostalgia and other frames commonly used in radical‐right discourse, including populism, two aspects of nationalism (exclusion and low pride), and authoritarianism, as measured in a recent study using the same corpus (Bonikowski et al. 2022). This follows from our earlier argument that nostalgia may serve as a mechanism that connects these discursive elements.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
See 1 more Smart Citation